The effect of sampling on young Malaysian children's food preference - Dahari, Zainurin (2010)
The objectives of this research are to determine the awareness of sample the young Malaysian children, identifying the preferred sample and determining the effect of sample on young Malaysian children's food preferences. Interview and experimentation have been used to collect the data. The samples were young Malaysian children aged five to six. The important findings were young Malaysian children being more attracted to the product offered with sample compared without sample. Food sample would be the most favorable choice among the young Malaysian children and it can be related to availability of attractive sample. The findings will open up a new dimension on the possibility of influencing young Malaysian children to purchase healthier food using sample.